Learning in non‐avian reptiles 40 years on: advances and promising new directions. (19th October 2020) - Szabo, Birgit; Noble, Daniel W. A.; Whiting, Martin J.
ABSTRACT: Recently, there has been a surge in cognition research using non‐avian reptile systems. As a diverse group of animals, non‐avian reptiles [turtles, the tuatara, crocodylians, and squamates (lizards, snakes and amphisbaenids)] are good model systems for answering questions related to cognitive ecology, from the role of the environment on the brain, behaviour and learning, to how social and life‐history factors correlate with learning ability. Furthermore, given their variable social structure and degree of sociality, studies on reptiles have shown that group living is not a pre‐condition for social learning. Past research has demonstrated that non‐avian reptiles are capable of more than just instinctive reactions and basic cognition. Despite their ability to provide answers to fundamental questions in cognitive ecology, and a growing literature, there have been no recent systematic syntheses of research in this group. Here, we systematically, and comprehensively review studies on reptile learning. We identify 92 new studies investigating learning in reptiles not included in previous reviews on this topic – affording a unique opportunity to provide a more in‐depth synthesis of existing work, its taxonomic distribution, the types of cognitive domains tested and methodologies that have been used. Our review therefore provides a major update on our current state of knowledge and ties the collective evidence together under nine umbrella research areas: ( i ) habituation of behaviour, ( ii ) animal training through conditioning, ( iii ) avoiding aversive stimuli, ( iv ) spatial learning and memory, ( v ) learning during foraging, ( vi ) quality and quantity discrimination, ( vii ) responding to change, ( viii ) solving novel problems, and ( ix ) social learning. Importantly, we identify knowledge gaps and propose themes which offer important future research opportunities including how cognitive ability might influence fitness and survival, testing cognition in ecologically relevant situations, comparing cognition in invasive and non‐invasive populations of species, and social learning. To move the field forward, it will be immensely important to build upon the descriptive approach of testing whether a species can learn a task with experimental studies elucidating causal reasons for cognitive variation within and among species. With the appropriate methodology, this young but rapidly growing field of research should advance greatly in the coming years providing significant opportunities for addressing general questions in cognitive ecology and beyond.